Original articleMalformations of cortical development in children: clinical manifestation, neuroimaging and neuropathology in selected cases - Emich-Widera, Ewa; Larysz, Dawid; Kluczewska, Ewa; Larysz, Patrycja; Adamek, Dariusz; Mandera, Marek; Marszał, Elżbieta (Folia Neuropathologica, 2006)
Cerebral cortical development can be divided into three steps: cellular proliferation, neuronal migration and organization. Based on known pathologic, genetic and neuroimaging features a classification for malformations of cortical development was proposed by Barkovich in 2001, and updated in 2005. Malformations of cerebral cortex development (MCCD) often demonstrate epileptic seizures and delay in psychomotor development. About 20–40% of children with epilepsy are drug-resistant and there is a large paediatric population requiring epilepsy surgery operations. In our work we performed clinical analysis of 68 children with MCCD treated in our hospital between 2000 and 2006. In our work to consider the type of MCCD we used the updated classification scheme proposed by Barkovich et al. We analyzed epilepsy, gestational and perinatal history, initial symptoms, time to establishing full diagnosis and neurodevelopmental/IQ status. In our results we found that despite similar clinical manifestation neuropathological basis could be significantly different, and vice versa: children with nearly identical neuropathological findings could have completely different neurological and radiological symptoms. Children with drug-resistant epilepsy are potential candidates for neurosurgical treatment; especially lesionectomies in such cases could be very promising in terms of epilepsy management and quality of life as well.